Comparative evaluation of smear layer removal efficacy of neem leaf extract, propolis, and orange oil when used as endodontic irrigants: An in vitro scanning electron microscopic study - Ria Setia; Nitika Bajaj; Meenu Bhola; Gurlal Singh Brar (Wolters Kluwer Medknow Publications, 2023)
Introduction: In root canal treatment, chemical debridement of the root canal with the help of irrigants is important due to the complex internal anatomy of the teeth. Biomechanical root canal preparation produces a smear layer. It covers the dentinal tubules, which may interfere with the penetration of various irrigants and intracanal medicaments, so the smear layer has to be removed. The potential side effects and certain limitations of chemical irrigants for smear layer removal have led to a shift toward herbal alternatives. Objective: The aim of the present study was to evaluate and compare the smear layer removal efficacy of Neem leaf extract, Propolis, and Orange oil as endodontic irrigants using the scanning electron microscope. Materials and Methods: Ninety samples were taken and then randomly (simple random sampling method) divided into three experimental groups (n = 30) depending upon different endodontic irrigants used: Group 1-Neem leaf extract, Group 2-Orange oil and Group 3-Propolis and smear layer removal evaluation was done under the scanning electron microscope Scanning Electron Microscope (SEM) at all the levels, i.e., coronal, middle, and apical. Results: The collected data were analyzed using the Chi-square test. Group 1 (Neem leaf extract) showed the highest smear layer removal efficacy, which was followed by Group 2 (Orange oil) and the least efficacy of smear layer removal was shown by Group 3 (Propolis) at coronal, middle, and apical levels. Conclusion: Group 1 (Neem leaf extract) performed significantly better in removing the smear layer at coronal, middle, and apical levels as compared to the other two groups.